Pengaruh Bentuk Pelayanan SDM, Fasilitas dan Promosi terhadap Kepuasan Pelanggan PT. Asia Sakti Wahid Foods Manufacture Medan - Sylvani, Sylvani; Merkury, Kenjie; Rangkuti, Dhita Adriani; Lubis, Andrew Satria (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of HR services, facilities and promotions on customer satisfaction at PT. Asia Sakti Wahid Foods Manufacture Medan. The population of this research includes all customers during the 2022 period. The sample was determined using accidental sampling technique, so that there were 100 respondents. The research results reveal that simultaneously and partially there is a positive and significant influence between the variables of HR services, facilities and promotions on customer satisfaction at PT. Asia Sakti Wahid Foods Manufacture Medan.